Importance of prognostic stratification via gene mutation analysis in elderly patients with acute myelogenous leukemia. (10th April 2019) - Fujiwara, Yusuke; Yamaguchi, Hiroki; Yui, Shunsuke; Tokura, Taichiro; Inai, Kazuki; Onai, Daishi; Omori, Ikuko; Marumo, Atsushi; Yamanaka, Satoshi; Sakaguchi, Masahiro; Terada, Kazuki; Nakagome, Shun; et al.
Abstract: Introduction: Acute myelogenous leukemia (AML) in elderly patients is associated with an increased incidence of complications and treatment‐related toxicity because of the frequency of comorbid disease and age‐related deterioration in organ function. Despite advances in AML treatment in recent years, elderly patients have experienced limited benefit, and their outcomes remain poor. This study aimed to perform a comprehensive gene mutation analysis in elderly AML patients and identify gene mutations that could serve as prognostic factors. Methods: An analysis of gene mutations was performed for 281 AML patients, including 98 elderly patients aged 65 years or above. Results: Compared to younger AML patients, elderly patients showed a higher frequency of the following gene mutations: TP 53 ( P = 0.026), PTPN 11 ( P = 0.006), RUNX 1 ( P = 0.024), TET 2 ( P = 0.002), and ASXL1 ( P = 0.023). The complete remission rate was significantly lower in DNMT3 A mutation‐positive cases (4.26%, P = 0.011) and TP 53 mutation‐positive cases (2.13%, P = 0.031) than in negative cases. The overall survival rate was significantly poorer in cases with FLT3 ‐ITD ( P = 0.003), DNMT3A ( P = 0.033), or TP53 mutation ( P < 0.001). Conversely, cases with PTPN11 mutation ( P = 0.014) had a significantly more favorable prognosis. In multivariate analysis, FLT3 ‐ITD ( P = 0.011) and TP53 mutation positivity ( P = 0.002) were independent poor prognostic factors, as were a performance status of 3 or above ( P < 0.001) and poor cytogenetic prognosis ( P = 0.001). In contrast, PTPN11 mutation positivity ( P = 0.023) was an independent favorable prognosis factor. Conclusion: Analysis of gene mutations in elderly AML patients is very important, not only for establishing prognosis, but also for introducing appropriate molecular‐targeted treatments.